The Contribution of Microorganisms to Soil Organic Carbon Accumulation under Fertilization Varies among Aggregate Size Classes - Lu, Jinjing; Li, Shengping; Liang, Guopeng; Wu, Xueping; Zhang, Qiang; Gao, Chunhua; Li, Jianhua; Jin, Dongsheng; Zheng, Fengjun; Zhang, Mengni; Abdelrhman, Ahmed Ali; Degré, Aurore (Agronomy (Basel), 2021)
Long-term fertilization alters soil microbiological properties and then affects the soil organic carbon (SOC) pool. However, the interrelations of SOC with biological drivers and their relative importance are rarely analyzed quantitatively at aggregate scale. We investigated the contribution of soil microbial biomass, diversity, and enzyme activity to C pool in soil aggregate fractions (>5 mm, 2–5 mm, 1–2 mm, 0.25–1 mm, and <0.25 mm) at topsoil (0–15 cm) from a 27-year long-term fertilization regime. Compared to CK (no fertilization management), NP (inorganic fertilization alone) decreased all of the microbial groups’ biomass, while NPS and NPM (inorganic fertilization plus the incorporation of maize straw or composted cow manure) significantly reduced this negative effect of NP on microbial biomass and increased the microbial contribution to C pool. The results show that microbial variables were significantly correlated with SOC content in >0.25 mm aggregates rather than in <0.25 mm aggregates. Fungal variables (fungal, AM biomass, and F/B ratio) and enzyme activities (BXYL and LAP) in >0.25 mm aggregates explained 21% and 2% of C, respectively. Overall, organic matter addition could contribute to higher C storage by boosting fungal community and enzyme activity rather than by changing microbial community diversity in macro-aggregates.